Predictors of knowledge sharing behaviour and mediating role of organisational commitment among Malaysian public service administrators - Tangaraja, Gangeswari (2016)
Fostering employees’ knowledge sharing behaviour (KSB) is an important agenda for the HRD practitioners in this knowledge era. This is because knowledge sharing has been identified as the most crucial process for effective knowledge management and has been associated to organisational performance. Although in recent years studies associated to knowledge sharing started to proliferate, however, the mediating effect of organisational commitment on the relationships between the intrinsic motivational factors (knowledge self-efficacy, enjoyment in helping others, public service motivation), extrinsic motivational factors (reciprocity, recognition practices), comfort factors (time availability, ICT support) and organisational socialisation factors (social network, trust) and KSB were poorly understood. Moreover, less focus was given to the administrators in the Malaysian public sector organisations. Therefore, to bridge these gaps and to gain new insights, this study aims to examine selected factors that influence KSB and the mediation effect of organisational commitment among the Malaysian public service administrators. The study theorised knowledge sharing using the General Workplace Commitment Model by Meyer and Herscovitch (2001) as the main underpinning theory and has integrated it with Three Component Model of Organisational Commitment (Meyer & Allen, 1991), Self Determination Theory (Deci & Ryan, 1985) and Social Capital Theory (Nahapiet & Ghoshal, 1998) to explain Malaysian public service administrators’ KSB. The present study employed a quantitative approach with correlational research design. In addition, it adopted a cross-sectional survey using structured questionnaires in data collection. A number of 231 Administrative and Diplomatic Service (ADS) Officers Grade M44 and above (the respondents) from various ministries/central agency of Malaysian public sector organisations in Putrajaya, the Federal Administrative Centre of Malaysia participated in this study. Their responses were analysed for descriptive statistics to determine the levels of all continuous variables involved in this study. As for the proposed hypotheses, the data were analysed using PLS-SEM. The analysis of descriptive statistic indicated that Malaysian public service administrators actively engage in KSB. The study revealed that intrinsic motivational factors (knowledge self-efficacy, enjoyment in helping others, PSM) are key factors in developing administrators’ affective commitment towards the organisation. Further, it showed that, organisational socialisation factors (trust, social network) are crucial factors in developing administrators’ normative organisational commitment. As a whole, the study found that affective organisational commitment is the key intermediate factor to enable intrinsically motivated administrators to engage in KSB. In addition, it was found that normative organisational commitment is pertinent intermediate factor to enable administrators who are socially connected in a trustworthy environment to engage in KSB.